2017
DOI: 10.1121/1.4986930
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive factors as predictors of accented speech perception for younger and older adults

Abstract: Though some studies suggest that older adults are not differentially impacted by foreign-accented speech relative to younger adults, other studies indicate that older adults are poorer at perceiving foreign-accented speech than younger adults. The present study sought, first, to clarify the extent to which older and younger adults differed in their perception of foreign-accented speech. The secondary aim was to elucidate the extent to which the cognitive mechanisms supporting accented speech perception differ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 36 publications
3
23
0
Order By: Relevance
“…We previously found that older adults were poorer than younger adults at perceiving foreign-accented speech [3], but that there was no difference between older and younger adults when perceiving dysarthric speech [4]. The current results expand on our previous findings by suggesting that even though older adults' performance may differ across speech types, common speech perception mechanisms may be at play.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…We previously found that older adults were poorer than younger adults at perceiving foreign-accented speech [3], but that there was no difference between older and younger adults when perceiving dysarthric speech [4]. The current results expand on our previous findings by suggesting that even though older adults' performance may differ across speech types, common speech perception mechanisms may be at play.…”
Section: Discussionsupporting
confidence: 69%
“…Our previous reports [3,4] indicated that older adults' perception of both accented and dysarthric speech was predicted by working memory capacity and by interactions between hearing acuity and inhibitory control. An interaction between hearing acuity and cognitive flexibility was only found for accented speech [3] whereas a main effect of cognitive flexibility and an interaction between hearing acuity and receptive vocabulary were only found in our investigation of dysarthric speech [4].…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Previous research suggests that understanding spoken language, particularly in difficult listening situations (e.g., speech in noise and foreign-accented speech), may be affected by age-related factors, including hearing loss and declines in cognitive function (e.g., Gordon-Salant & Fitzgibbons, 2004;Gordon-Salant, Yeni-Komshian, & Fitzgibbons, 2010;Wingfield, Tun, & McCoy, 2005). Indeed, relative to younger adults, older adults, with and without hearing loss, experience greater difficulty understanding speech in noise and foreign-accented speech (e.g., Dubno, Dirks, & Morgan, 1984;Gordon-Salant & Fitzgibbons, 1995;Ingvalson, Lansford, Fedorova, & Fernandez, 2017;Schneider, Daneman, Murphy, & See, 2000;Souza, Arehart, Shen, Anderson, & Kates, 2015). In addition, the cognitive mechanisms supporting perception of speech in difficult listening conditions may be different for younger and older adults.…”
mentioning
confidence: 99%